2013
DOI: 10.1186/1472-6920-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Medical School Attrition-Beyond the Statistics A Ten Year Retrospective Study

Abstract: BackgroundMedical school attrition is important - securing a place in medical school is difficult and a high attrition rate can affect the academic reputation of a medical school and staff morale. More important, however, are the personal consequences of dropout for the student. The aims of our study were to examine factors associated with attrition over a ten-year period (2001–2011) and to study the personal effects of dropout on individual students.MethodsThe study included quantitative analysis of completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 33 publications
(117 reference statements)
6
86
1
12
Order By: Relevance
“…Nevertheless, considering only the first three years of studies between both samples, which are comparable to each other in study duration, the difference in the average of dropout percentages between both curriculum designs is remarkable – which prompted us to show these data and discuss what might have caused the attrition reduction. The implication of this finding is that it corroborates similar findings in a few other studies that have shown that the curriculum design seems to influence students’ dropout rates [6,7,10,2325]. However, little is known about the role curriculum designs play in dropping out [26].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Nevertheless, considering only the first three years of studies between both samples, which are comparable to each other in study duration, the difference in the average of dropout percentages between both curriculum designs is remarkable – which prompted us to show these data and discuss what might have caused the attrition reduction. The implication of this finding is that it corroborates similar findings in a few other studies that have shown that the curriculum design seems to influence students’ dropout rates [6,7,10,2325]. However, little is known about the role curriculum designs play in dropping out [26].…”
Section: Discussionsupporting
confidence: 86%
“…Dropping out usually has negative consequences on social, personal, financial and educational aspects of students’ lives, constituting a reason of great concern in medical schools [10,18]. Since dropping out represents an important educational problem, plenty of information on calculating the percentage of admitted students that drop out of medical school without completing their studies exists in the available literature [4,1922].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Against the backdrop of a challenging economic environment, Ireland's health system has experienced significant budgetary pressure and this has produced a decrease in front-line staff morale and an increase in international migration. 7,8 Irish trainee doctors have referred to feeling undervalued by the system and have reported fatigue as well as heightened anxiety regarding clinical performance and decision-making skills. 8 These pressures are heightened by the recent shift in the role expectations of doctors, which has expanded beyond clinical knowledge and skills to include team management, administration and use of electronic records.…”
Section: Introductionmentioning
confidence: 99%